A Moment-to-Moment Analysis of Trust in Agricultural Messages - Lauren Elizabeth LaGrande; Courtney Meyers; R. Glenn Cummins; Matt Baker (Journal of Applied Communications, 2021)
Consumers have varying levels of trust in agricultural production practices, which can influence attitudes, shift opinions, and change behaviors. The purpose of this study was to determine what agricultural messages are considered the most trustworthy among consumers and what differences exist among five dimensions of trustworthiness. With a pro-agriculture video as the stimulus, this study used continuous response measurement (CRM) to collect data from 151 post-secondary students who were randomly assigned to evaluate one of five trustworthiness dimensions (trust, honest, sincere, dependable, reliable). Participants used handheld dials to continuously rate their evaluation of the messages in the video then completed a questionnaire to provide additional insights. Overall, participants trusted agricultural messages, although some specific phrases were rated more positively than others. Participants had more trust in messages that portray agriculture as a family endeavor and create connection between producers and consumers. Participants indicated skepticism in messages revolving around farmer/rancher motivation in agriculture. The results support the importance of strategically tailoring and crafting effective messages. Recommendations for future practice and research are discussed.
Keywords: dial testing; continuous response measurement; message testing; trust; moment-to-moment analysis